ADVANTAGES AND DISADVANTAGES OF IMMITATION TRAINING (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The article deals with topical issues of simulation training in the course of training practices of medical University. The task of the educational process at the medical University is to form practical skills of students from the first year with the help of simulation training.